"May the angels lead you into Paradise": staging the Cluniac liturgy in medieval Hispanic priories. Issue 2 (3rd July 2017) - Senra, José Luis
ABSTRACT: In this article, I analyze the impact that Cluny's strict liturgical demands had on the planning of a priory that was being newly built at the turn of the twelfth century. My hypothetical reconstruction of San Zoilo de Carrión de los Condes, the most important Cluniac priory in Iberia, is made possible thanks to new information from archaeology and unpublished documentary sources. These allow us to comprehend the elaborate setting that was devised for the Cluniac liturgy. The church of San Zoilo had a monumental west end and a cloister with all its dependencies; this complex was laid out in such a manner as to allow a complete processional circuit. In part, this design grew out of the desire to create a space for elite memorialization. The present article compares San Zoilo with contemporary monastic centers that were also influenced by Cluny – the monastery of Santos Facundo y Primitivo de Sahagún and the priory church of San Martín de Frómista – in an effort to deepen our understanding of the features employed by the great Cluniac possessions in medieval Iberia to define themselves.